Produksi dan Kontribusi Pemanfaatan Arang Alaban (Vitex pubescens) pada Pendapatan Masyarakat Desa Gohong Kabupaten Pulang Pisau: Production And Contribution of Charcoal Utilization Alaban (Vitex pubescens) On Income of Gohong Village Community in Pulang Pisau Regency - Nursiah, Nursiah; Rosdiana, Rosdiana; Rahmawati, Reni; Kahayani, Wayan Dini Apri (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2024)
Charcoal is one solution to minimize dependence on fossil fuel use, as charcoal is considered cheaper and can be continuously produced because its raw materials come from renewable wood. One type of wood used to make charcoal is Alaban wood (Vitex pubescens). The aim of this study is to analyze the production and utilization of Alaban charcoal used by the people of Gohong Village and to analyze the income level and contribution of Alaban charcoal to the income of the people of Gohong Village. The necessary data includes production, utilization, production costs, total receipts from Alaban charcoal production, selling price, income from Alaban charcoal production, and income from other than Alaban charcoal production. The results of the study showed that the total production of Alaban charcoal was 8,016 sacks/year with a weight of 25 kg/sack. The total income from Alaban charcoal production was Rp 138,884,000/year with an average respondent income of Rp 10,683,385/year. The contribution of Alaban charcoal production to the respondents' income was in the small income contribution category, which was 36.11%, so the average production of Alaban charcoal was used as a side job by respondents for additional income. This Alaban charcoal business can create jobs if done regularly.